2007
DOI: 10.1002/pssc.200674409
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence from porous layers produced by Ag‐assisted electroless etching

Abstract: Porous layers were formed on highly resistive p-type silicon by an Ag-assisted electroless etching method using a chemical solution of HF and K 2 Cr 2 O 7 . The porous silicon (PS) layer formed by this method as a function of etching time was investigated by scanning electron microscopy (SEM) and backscattering spectrometry (BS) in random and channelling mode. Channelling spectra show that the porous layer remains crystalline after etching. On the other hand, random and channelling spectra show that the deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…261,270,278 It is interesting that PL of PSi prepared using metal assisted etching has specific features in comparison with PSi prepared using anodic etching. Hadjersi and Gabouze 277 have shown that the evolution of PL intensity with etching time can be divided into two phases. In the first phase the emission is in the blue region.…”
Section: Metal-assisted Etchingmentioning
confidence: 99%
See 2 more Smart Citations
“…261,270,278 It is interesting that PL of PSi prepared using metal assisted etching has specific features in comparison with PSi prepared using anodic etching. Hadjersi and Gabouze 277 have shown that the evolution of PL intensity with etching time can be divided into two phases. In the first phase the emission is in the blue region.…”
Section: Metal-assisted Etchingmentioning
confidence: 99%
“…Moreover, using metal-assisted stain etching porous silicon layers have been formed on highly resistive silicon, which are difficult to produce by the electrochemical etching. 277 Furthermore, compared to stain etched layers, galvanically formed porous layers have better uniformity and much bigger thickness. 261 Last years this method was successfully used in photonic, photovoltaic, or diffusion membrane applications.…”
Section: Advantages and Disadvantages Of Metal-assisted Stainmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal-assisted etching is frequently used to prepare photoluminescent porous Si (Dimova-Malinovska et al 1997;Li and Bohn 2000;Harada et al 2001;Chattopadhyay et al 2002;Hadjersi et al 2004, Hadjersi et al 2005bHadjersi 2007;Megouda et al 2009b;Zhao et al 2007;Gorostiza et al 1999;Chattopadhyay and Bohn 2006;Hadjersi and Gabouze 2007;Lipinski et al 2009). MAE displays little crystallographic dependence and can be performed on crystalline or multicrystalline Si substrates, and the various Si morphologies and nanomicrostructures obtained are promising for photovoltaic applications in several areas: antireflective coating (Yae et al 2003(Yae et al , 2005(Yae et al , 2006Peng et al 2005a, b;Benoit et al 2008;Lu and Barron 2013;Tsujino and Matsumura 2006b;Chaoui et al 2008;Nishioka et al 2008Nishioka et al , 2009Srivastava et al 2010;Cao et al 2011;Kim et al 2011Kim et al , 2012Geng et al 2012;Wang et al 2013b;Li et al 2013a), texturization for multicrystalline wafers (Tsujino and Matsumura 2006a;Waheed et al 2010;Branz et al 2009;Li et al 2012;Wan et al 2008;Koynov et al 2006Koynov et al , 2007Lipiński 2008;…”
Section: Applicationsmentioning
confidence: 99%
“…However, it provides PL intensities in an order of magnitude smaller than conventional electrochemically etched PS [5]. Recently, we have used a new metal-assisted electroless etching method [6], developed previously by Li and Bohn [7] to produce visible-light-emitting layers. It needs no electrodes on the back surface of silicon wafers and enables formation of uniform porous silicon layers.…”
Section: Introductionmentioning
confidence: 99%